The Influence of Realistic Mathemathic Education Model on Mathematical Reasoning Ability Viewed from Student Learning Styles - Dini Apriani; Mujib Mujib; Dona Dinda Pratiwi (UIN Sumatera Utara, 2018)
This study aims to see the effect of realistic mathemathic education models on students' mathematical reasoning abilities in terms of learning styles. This type of research is quantitative. Data collection techniques used are essay tests and interviews. The data analysis technique used is hypothesis testing using anava 2 roads. However, before the anova test is carried out, the normality, homogeneity and balance test are carried out first. Based on the data that has been known that normal data, based on the same and balanced variance, the 2-way ANOVA test results show that there is an influence of the RTE model on students' mathematical reasoning ability, namely the reasoning ability of students with the RME model treatment is better than mathematical reasoning ability with conventional treatment methods. In addition, there is the influence of student learning styles on students' reasoning abilities.